Marked Reduction of Socioeconomic and Racial Disparities in Invasive Pneumococcal Disease Associated With Conjugate Pneumococcal Vaccines. (11th August 2020) - Raman, Rameela; Brennan, Julia; Ndi, Danielle; Sloan, Chantel; Markus, Tiffanie M; Schaffner, William; Talbot, H Keipp
Abstract: Background: It is not known whether reductions in socioeconomic and racial disparities in incidence of invasive pneumococcal disease (defined as the isolation of Streptococcus pneumoniae from a normally sterile body site) noted after pneumococcal conjugate vaccine (PCV) introduction have been sustained. Methods: Individual-level data collected from 20 Tennessee counties participating in Active Bacterial Core surveillance over 19 years were linked to neighborhood-level socioeconomic factors. Incidence rates were analyzed across 3 periods—pre–7-valent PCV (pre-PCV7; 1998–1999), pre–13-valent PCV (pre-PCV13; 2001–2009), and post-PCV13 (2011–2016)—by socioeconomic factors. Results: A total of 8491 cases of invasive pneumococcal disease were identified. Incidence for invasive pneumococcal disease decreased from 22.9 (1998–1999) to 17.9 (2001–2009) to 12.7 (2011–2016) cases per 100 000 person-years. Post-PCV13 incidence (95% confidence interval [CI]) of PCV13-serotype disease in high- and low-poverty neighborhoods was 3.1 (2.7–3.5) and 1.4 (1.0–1.8), respectively, compared with pre-PCV7 incidence of 17.8 (15.7–19.9) and 6.4 (4.9–7.9). Before PCV introduction, incidence (95% CI) of PCV13-serotype disease was higher in blacks than whites (17.3 [15.1–19.5] vs 11.8 [10.6–13.0], respectively); after introduction, PCV13-type disease incidence was greatly reduced in both groups (white: 2.7 [2.4–3.0]; black: 2.2 [1.8–2.6]). Conclusions: Introduction of PCV13 was associated with substantial reductions in overall incidence and socioeconomic and racial disparities in PCV13-serotype incidence. Abstract : In this laboratory- and population-based study, we describe how the introduction of 13-valent pneumococcal conjugate vaccine (PCV13) is associated with substantial reductions in both overall incidence and socioeconomic and racial disparities in vaccine-type invasive pneumococcal disease incidence, representing a major public health achievement.